2011
DOI: 10.1007/s13273-011-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

A safety assessment of phototoxicity and sensitization of SiO2 nanoparticles

Abstract: Despite widespread use of silicon dioxide (SiO 2 ) NPs in industry and in our daily lives, no studies so far have evaluated the potential of their skin phototoxicity and sensitization. This study was designed to investigate the potential of phototoxicity and sensitization of SiO 2 NPs. Assessment of the potential of skin phototoxicity was carried out using the 3T3 neutral red uptake test, an HSEM, and an animal model. The potential of skin sensitization was evaluated by a non-radioisotope local lymph node assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Topically applied nanoparticles are utilized in the medical field to detect and treat diseases as their size is similar to that of biological molecules . Over the past decade, QDs, which are semiconductor nanocrystals, have gained a great deal of attention and QDs have been developed for use in a broad range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…Topically applied nanoparticles are utilized in the medical field to detect and treat diseases as their size is similar to that of biological molecules . Over the past decade, QDs, which are semiconductor nanocrystals, have gained a great deal of attention and QDs have been developed for use in a broad range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 SiO 2 (silica) nanoparticles are being utilized in a wide range of industrial applications, including as thickening agents, desiccants, toothpaste additives, and adsorbents. [15][16][17][18] With the increase in the demand for and production of nanomaterials, the general public will have a higher possibility of being exposed to engineered nanomaterials. Thus, the Working Party on Manufactured Nanomaterials (WPMN) of the Organization for Economic Cooperation and Development (OECD) selected 14 nanomaterials to analyze for potential human health risks.…”
Section: Introductionmentioning
confidence: 99%
“…8 SiO 2 nanoparticles have been widely used in a variety of industrial fields, including the plastics, rubber, ceramics, coatings, adhesives, and medical industries. 9,10 Numerous studies have reported the cytotoxicity, genotoxicity, and alterations in protein expression associated with SiO 2 nanoparticles in both in vitro and in vivo systems. 11,12 Further, it has been suggested that the genotoxicity caused by SiO 2 nanoparticles may be due to proinflammatory effects, modification of chromatin structure, and liberation of DNase or a potent inducer of cytogenetic damage.…”
Section: Introductionmentioning
confidence: 99%